Tax expenditure reporting: towards a more transparent government budget - Yussof, Salwa Hana; Kasipillai, Jeyapalan (2015)
Tax expenditures are a substitute to government direct spending. Therefore, they should be reported and analysed on the spending side of the budget. Failure to understand the concept of tax expenditures would lead to tax expenditures being mistakenly analysed as the revenue function and escaped the detailed scrutiny that should have been placed on direct spending. This article explores the concept of tax expenditures as posited by the late Professor Stanley S Surrey. It also discusses the arguments that oppose and support the use of tax expenditures, and the different methods that can be applied to measure tax expenditures in monetary terms. Finally, this article discusses the importance of tax expenditure reporting from a revenue perspective and outlines the steps involved in the preparation of a tax expenditure report.